(untitled) (Research, Society and Development, 2021)
The main objective of this article is to list the strategic alliances in a Third Sector organization, considering Sustainable Development Objective 17, as sources of resources to strengthen the institution through its civil society partners. To this end, a theoretical framework was developed on the definition and theories of strategic alliances, a discussion about the Third Sector has been included and the analysis of the Sustainable Development Goals 17. The approach adopted was exploratory and qualitative descriptive. For data collection, a survey-style questionnaire was adopted, in which preliminary information from the institution is collected, and interviews were conducted with semi-structured scripts, being a case study of a specific project developed by the entity. The results has showed that the studied institution successfully carries out its strategies to consolidate alliances with its partners, increasingly motivating this relationship.